Pemilihan Groin dan Breakwater sebagai Bangunan Pengaman Pantai Tiram Padang Pariaman - Yusuf, Muhammad; Mera, Mas (Jurnal Talenta Sipil, 2025)
This study is about numerical simulations to predict the effectiveness of groynes and breakwaters as protective structures for Tiram Beach, Padang Pariaman Regency (West Sumatra-Indonesia) using an existing software for abrasion management. The effectiveness of a shore-protective structure can be seen based on the bathymetry formed due to the structure. The numerical simulation is carried out at maximum wave conditions, with the dominant direction of the incoming wave in the deep sea being from the west. The simulation are carried out with 2 scenarios, namely with the addition of groynes (scenario 1), and with the addition of breakwaterse (scenario 2. The simulation time is only 5 days, starting from May 22 to May 26, 2020 because at that time the waves were extreme. The simulation results show that the breakwaters with a length of 80m and a distance of 70m from the shoreline are more effective in protecting Tiram Beach from abrasion. The simulation using groynes is only effective at holding sediment transport along the structures. The groynes are also unable to reduce wave energy coming from the west.